EVALUASI PEMBELAJARAN LEMBAGA PENDIDIKAN ISLAM DI ERA DIGITAL DI MI ALAM AL-ALY-SUKOMORO-NGANJUK - Muhammad Khisnun Himawan (CV. ADIBA AISHA AMIRA, 2025)
The digital transformation in the education sector has compelled Islamic educational institutions to integrate technology into all aspects of learning, including evaluation systems. This study aims to analyze the implementation model, development strategies, as well as the benefits and challenges of digital-based learning evaluation at MI Alam Al-Aly Sukomoro, Nganjuk. This research employs a qualitative field study method with a descriptive approach, conducted through direct observation and in-depth interviews with the school principal and teachers. The findings reveal that MI Alam Al-Aly adopts a hybrid approach to evaluation, combining both conventional and digital methods. Digital evaluation is implemented primarily in upper-grade classes using platforms such as Google Forms, while lower-grade students continue to be assessed through written and oral evaluations. Development strategies are carried out through participatory and collaborative approaches among teachers. The evaluation process reflects the Islamic educational principles of al-Kamāl (perfection), Istimrār (continuity), and Muḍū‘iyyah (objectivity). Although digital evaluation offers benefits in terms of efficiency and accessibility, it also encounters challenges such as limited access to digital devices and low digital literacy levels. Despite these obstacles, the institution demonstrates an adaptive model of evaluation that maintains core Islamic values while embracing technological advancement.